Agroforestry: Four decades of research development - Dagar, Jagdish C. (Indian Journal of Agroforestry, 2020)
Agroforestry is as old as agriculture itself. Many of the anecdotal agroforestry practices, which are time tested and evolved through traditional indigenous knowledge, are still being followed in different agro-ecological zones. The traditional knowledge and the underlying ecological principles concerning indigenous agroforestry systems around the world have been successfully used in designing the improved systems. Many of them such as improved fallows, home gardens, park systems, and alley cropping have evolved as modern agroforestry systems. During past four decades, agroforestry has come of age and begun to attract the attention of the international scientific community, primarily as a means for sustaining agricultural productivity in marginal lands and solving the second generation problems such as secondary salinization due to waterlogging and contamination of water resources due to use of excess nitrogen fertilizers and pesticides. Research efforts have shown that most of the degraded areas including eroded lands; saline, waterlogged and perturbation ecologies like mine spoils; and coastal degraded mangrove areas can be made productive by adopting suitable agroforestry techniques involving highly remunerative components such as plantation-based farming systems, high value medicinal & aromatic plants, livestock, poultry, forest and fruit-trees and vegetables. New concepts such as integrated farming systems; and urban and peri-urban agroforestry have emerged. Consequently, the knowledge-base of agroforestry is being expanded at a rapid pace. It is both a challenge and an opportunity to scientific community working in this inter-disciplinary field. In order to prepare themselves better for facing future challenges and seizing the opportunities, scientists need access to synthesized information and develop technologies to assess the environmental benefits we get from different agroforestry services. The global community has to recognize the potential benefits of many underexploited systems to address the most intractable land-management problems of the 21st century, such as food and nutrient security, climate change mitigation and adaptation, biodiversity conservation, and rehabilitation of degraded ecosystems. As we move forward to vigorously exploit these potential benefits, we will witness the involvement of agroforestry and its progress for solving these problems and be able to ensure food and environmental security at global level.